A new species of Olixon Cameron, 1887 (Hymenoptera: Rhopalosomatidae) and new records for the genus in Brazil - Bulbol, Mayara Medeiros; Bartholomay, Pedro Reck; Oliveira, Márcio Luiz De; Somavilla, Alexandre (Zootaxa, 2023)
Olixon Cameron, 1887 is a genus of solitary wasps belonging to Rhopalosomatidae with 28 species worldwide, all of which are distinct being brachypterous and having the inner eye margins straight. In this paper, we describe Olixon pantanensis Bulbol, Bartholomay & Somavilla sp. nov., based on a male from the Brazilian Pantanal biome and provide new distribution records for O. testaceum Cameron, 1887 in the country. We also provide the first descriptions and illustrations of the male genitalia for both species.